Molecular characterization of the thermally labile fraction of biochar by hydropyrolysis and pyrolysis-GC/MS - Rombolà, Alessandro G.; Fabbri, Daniele; Meredith, Will; Snape, Colin E.; Dieguez-Alonso, Alba (Elsevier, 2016)
Agroenvironmental benefits and limitations of biochar in soil applications require a full understanding of the stability and fate of the various carbon fractions. Analytical hydropyrolysis (HyPy) enables the determination of the stable black carbon (BCHyPy) and thermally labile (semi-labile; non-BCHyPy) fractions in biochar and soil samples. The non-BCHyPy fraction can be analysed at a molecular level by gas chromatography-mass spectrometry (GC-MS). In the present study, HyPy was applied to the characterisation of biochars produced from pine wood, beech wood and corn digestate with the same pyrolysis unit at low (340–400 °C) and high (600 °C) temperatures. Results were compared with those from Py-GC-MS. HyPy provided consistent information concerning the thermal stability of biochar samples, with BCHyPy levels related with the relative abundance of the charred fraction estimated by Py-GC-MS and the hydrogen/carbon (H/C) ratios. The non-BCHyPy fractions were featured by the presence of polycyclic aromatic hydrocarbons (PAHs) from two to seven rings, including alkylated derivatives up to C4. Partially hydrogenated PAHs were also detected. The yields of non-BCHyPy were higher for those biochars produced at lower temperatures and always more abundant than the levels of solvent-extractable PAHs. The methylated/parent PAH ratios from HyPy and Py-GC-MS exhibited lower values for the most charred biochar. The observed differences in the abundance of the stable fraction and the molecular chemistry of the semi-labile fraction can be usefully utilised to drive the process conditions to the desired properties of the resulting biochars and to predict the impact of biochar amendment to soil organic pools. The concentrations of priority PAHs in the semi-labile fraction was evaluated in the mg g−1 level suggesting that it could be an important fraction of the polyaromatic carbon pool in soil.